The Effect of Reward and Punishment on Employee Performance at PT Tunas Dwipa Matra Branch Raden Intan Bandar Lampung - Ranury, Dewi; Saputra, Febrian Eko (Universitas Pamulang, 2024)
This research aims to test and analyze the influence of Reward and Punishment on Employee Performance at PT. Tunas Dwipa Matra, Raden Intan Branch, Bandar Lampung. The population in this study was 110 employees of PT. Tunas Dwipa Matra, Raden Intan Branch, Bandar Lampung. The sample used in this research uses a non-probability sampling technique. The selected method is saturated sampling, which is a sampling method when all members of the population are used as samples. The results of this research indicate that the Reward variable partially has a positive and significant effect on Employee Performance at PT. Tunas Dwipa Matra Raden Intan Bandar Lampung Branch, so the first hypothesis is accepted. The Punishment variable partially has a positive and significant effect on employee performance at PT. Tunas Dwipa Matra Raden Intan Bandar Lampung Branch, so the second hypothesis is accepted. The results of this research also show that the Reward and Punishment variables together have a positive and significant effect on employee performance at PT. Tunas Dwipa Matra Raden Intan Bandar Lampung Branch, this means that the third hypothesis is accepted. Meanwhile, based on the coefficient of determination (R2) of 0.529 or 52.9%. This shows that 52.9% of the influence can be explained by the independent variables (Reward and Punishment) on the dependent variable (Employee Performance), while the remaining 47.1% is explained by other variables not tested in this research.